Influencia de la combinación de dosis de los fertilizantes complementarios Viosil y Yaramila sobre el cultivo del maíz H. DK 5005. - Intriago Mendoza, María Carolina (2008)
This investigation had as objective to increase the productivity and to provide of the main mineral elements that it requires the hybrid of com dekald 5005, with the fertilizers complementary viosil and yaramila in three different dosages. The experiment was carried out during the time of summer of the 2007 in the Campus of the Agricultural Polytechnic Superior School of Manabi Manuel Felix Lopez", where experimental units were evaluated tried with Viosil (V) in dose of 16.33, 20.41 and 24.49 liter (L) for hectare (there is); Yaramila (Y) in dose of 65.35, 81.63 and 97.96 kilograms (kg) for there is, besides a witness with complete fertilizer 15-15-15. They were carried out -10 treatments with four repetitions in a Design of Complete Block at random (DBCA) prepared in factorial arrangement of (3x3)+1. For the factor A, it was obtained the non significance as a result (ns) in the studied variables; plant height, 1 number of ears, diameter, longitude, grain weight and yield; obtaining a similar average of each variable with the levels of respective dosages, to exception of weight of 100 grains that analyzed statistically he/she gave a significant value, with a bigger value of 34.36 grams (gY in 100 grains. For the factor B the variable number of grains for ear, presented highly significant and significant differences. The level that he obtained the best yield was the Y2 (81.63 kg/ha). The interactions of the ear number for plants, number of grains for ear and weight of 100 grains was obtained a significant influence at statistical level but none justified the production cost confronting it with the treatment witness (T) at economic level. That happened in field showed that the H. DK-5005 with their genetic potential described by more Pronaca the complete payment 15-15-15 distributed in two application frequencies (10-30 dds) it is enough to nurture this cultivation; for what is necessary to base the selection and dosage of a fertilizer on the respective physical-chemical analyses of floor and also to take into account the technical recommendations of the houses producers of the fertilizers. Regarding the economic analysis, the treatment with a better marginal return was the witness (T) obtaining 970,30%, that is to say that for each invested dollar it is obtained $9,70, showing you as -that of better result from i he economic point of view.